Optimizing the Instillation of Noble Moral Values in Children Aged 5–6 - Naena Suhailah; Masganti Sit (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2026)
This study aims to examine the optimization of instilling noble moral values in children aged 5–6 years at RA Fajar Shiddiq and RA Azrina in Medan. The background of this study is based on the importance of character building in children from an early age through the cultivation of noble moral values such as politeness, honesty, discipline, responsibility, empathy, and cooperation. This study employed a qualitative descriptive method with 7 teachers as subjects. Data collection techniques included open-ended questionnaires, in-depth interviews, and classroom observations, while data analysis utilized the Miles and Huberman model, which encompasses data reduction, data presentation, and drawing conclusions through data triangulation to ensure validity. The results of the study indicate that the instillation of noble moral values has been consistently implemented through daily habit-forming activities at school, such as greeting teachers, sharing with peers and teachers, apologizing, maintaining discipline, and cooperating during play. Teachers play a crucial role as role models, mentors, and providers of positive reinforcement in shaping children’s character. Observation results also indicate positive behavioral development in children, marked by increased politeness, caring, independence, and the ability to cooperate. Although challenges exist, such as differences in children’s personalities and the influence of external environments, the instillation of noble moral values generally proceeds well and effectively in shaping the character of young children